Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

EL QUE ME AYUDE CON ESTO LE DOY CORONA ._.

TEMA : TEORIA DE EXPONENTES

- Al aplicar la ley de exponentes la expresión se reduce a:


EL QUE ME AYUDE CON ESTO LE DOY CORONA TEMA TEORIA DE EXPONENTES Al Aplicar La Ley De Exponentes La Expresión Se Reduce A class=

Sagot :

Answer:

S = [tex]\frac{36}{25}[/tex]

Step-by-step explanation:

Given expression is,

S = [tex]\sqrt[3]{[(\frac{3}{2})^{-2}+6^{-3}+(\frac{3}{2})^{-3}-6^{-1}}]^{-2}[/tex]

S = [tex]\sqrt[3]{[(\frac{2}{3})^{2}+(\frac{1}{6})^{3}+(\frac{2}{3})^{3}-(\frac{1}{6})}]^{-2}[/tex]

   = [tex]\sqrt[3]{[\frac{4}{9}+\frac{1}{216}+\frac{8}{27}-\frac{1}{6}}]^{-2}[/tex]

   = [tex]\sqrt[3]{(\frac{96+1+64-36}{216})^{-2}}[/tex]

   = [tex]\sqrt[3]{(\frac{125}{216})^{-2}}[/tex]

   = [tex]\sqrt[3]{(\frac{216}{125})^{2}}[/tex]

   = [tex]\sqrt[3]{(\frac{216}{125})\times (\frac{216}{125})}[/tex]

   = [tex]\sqrt[3]{(\frac{6\times 6\times 6}{5\times 5\times 5})\times (\frac{6\times 6\times 6}{5\times 5\times 5})}[/tex]

   = [tex]\sqrt[3]{(\frac{6}{5})^3\times (\frac{6}{5})^3}[/tex]

   = [tex]\frac{6}{5}\times \frac{6}{5}[/tex]

   = [tex]\frac{36}{25}[/tex]